Upaya Perbaikan Pendapatan Peternak Sapi Pembibitan di Kecamatan Moyo Utara, Kabupaten Sumbawa, NTB - Hermansyah; Fachry, Anwar; Nugroho, M. Prasetyo; Yanuarianto, Oscar; Noersidiq, Azhary; Taqiuddin, Moh.; Dilaga, Syamsul Hidayat (Universitas Mataram, 2025)
This community service activity aims to increase farmers' income as feed for breeding cattle and is intended as a step to save the environment from the effects of erosion due to massive land clearing that has occurred in recent years, including in Moyo Utara District, Sumbawa Regency, West Nusa Tenggara Province. In addition to providing material through short training on seedling selection procedures, breeding patterns, harvesting and utilization techniques of Lamtoro taramba, farmers are also encouraged to calculate the economic value of cattle breeding by utilizing lamtoro taramba compared to using other feed crops such as grass and agricultural waste. The results of the service showed that the application of lamtoro taramba on a limited scale showed better growth of breeding cattle and that the plant is beneficial in cattle breeding efforts. In turn, lamtoro taramba is no longer perceived as a land-destroying pest. Lamtoro taramba opens up opportunities for the Sumbawa Regency Government to provide holistic livestock development that leads to an increase in farmers' income